The Effect of Ease and Intensity of Promotion on Interest in Using BNI Wondr QRIS - Cinta Anasilla Wulan Haqi; Sri Trisnaningsih (Manunggal Halim Jaya, 2026)
This study examines the influence of ease of use and promotion intensity on the intention to use BNI Wondr QRIS among accounting students at UPN Veteran East Java. The rapid growth of fintech in Indonesia has encouraged the digitization of transactions, including through QRIS. Although efficient in financial recording, research gaps remain regarding factors influencing the intention to use QRIS among accounting students with a strong understanding of financial systems. This quantitative study employed a survey method involving 91 students from the 2021–2023 cohorts, selected through simple random sampling. Data were collected via an online questionnaire and analyzed using SPSS version 30. Results indicate that both ease of use and promotion intensity have a positive and significant partial and simultaneous effect on students' intention to use BNI Wondr QRIS. Ease of use was measured through efficiency and clarity of transaction processes, consistent with the Technology Acceptance Model (TAM). Promotional efforts such as discounts and cashback generated user interest, aligning with the AIDA model. These findings highlight the importance of simplifying access and implementing targeted promotions to increase QRIS adoption among Generation Z students. This study contributes to QRIS BNI's marketing strategies and a better understanding of digital financial technology adoption in academic settings.